The number of breeders explains genetic connectivity in an endangered bird. Issue 11 (18th June 2019) - Robertson, Ellen P.; Fletcher, Robert J.; Austin, James D.
Abstract: Connectivity is central to ecology and evolution as it focuses on the movement of individuals or genes across landscapes. Genetic connectivity approaches aim to understand gene flow but often estimate it indirectly based on metrics of genetic differentiation, which can also be affected by other evolutionary forces such as genetic drift. Gene flow and genetic drift are driven by separate ecological mechanisms with potentially differing effects on genetic differentiation and interpretations of genetic connectivity. The ecological mechanisms contributing to gene flow and genetic drift are primarily effective dispersal, or movement followed by successful reproduction, and the number of breeders in a local population, N b, respectively. Yet, rarely are these ecological mechanisms and genetic connectivity measured simultaneously across landscapes. We examine the roles of effective dispersal and N b on genetic connectivity across the entire range of the endangered snail kite ( Rostrhamus sociabilis plumbeus ), between 2006–2015. We find that both N b and effective dispersal are important predictors of genetic connectivity across this landscape, but that N b has a 3 × stronger effect on genetic connectivity. Furthermore, N b is positively correlated with heterozygosity and allelic richness within patches, suggesting a potentially important role of genetic drift, in addition to gene flow, on genetic connectivity. These results emphasize that conservation efforts should focus on not only between‐patch processes of movement but also within‐patch processes regarding habitat quality and local population size for increasing genetic connectivity.